Violência doméstica contra as mulheres: pensando o acolhimento psicossocial como suporte para saída situação de violência - Santos, Josiane Matos dos (2024)
The present study aims to understand, through conversations with women who sought assistance from the Women's Reference Center (CEREM) during the COVID 19 pandemic, what their experience was like in the initial assistance they received when seeking formal help. Additionally, it seeks to foster a discussion that contributes to the development of issues and possibilities related to this initial contact and its specificities, highlighting psychosocial support as a useful tool, as this initial assistance can be considered crucial in reducing women's exposure to violence. Thus, data collection was conducted through individual and semi-structured interviews. As a methodology for analyzing the interviews, we will use discourse analysis. This method does not aim to analyze the subject's discourse in isolation, disregarding the various contexts involved. On the contrary, it enables examination of how discourse is constructed and how it influences and is influenced by society, ideology, and power relations